Patricio Ortiz, Indigenous Knowledge, Education and Ethnic Identity: An Ethnography of an Intercultural Bilingual Education Program in a Mapuche School in Chile. Saarbrücken, Germany: VDM-Verlag, 2009, 220 páginas - Martinez Berrios, Nelson (Polis (Santiago), 2018)
.